2016
DOI: 10.1103/physrevd.94.063536
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum cosmology of the little rip abrupt event

Abstract: We analyze from a classical and quantum point of view the behavior of the universe close to a little rip, which can be interpreted as a big rip sent towards the infinite future. Like a big rip singularity, a little rip implies the destruction of all bounded structure in the Universe and is thus an event where quantum effects could be important. We present here a new phantom scalar field model for the little rip. The quantum analysis is performed in quantum geometrodynamics, with the Wheeler-DeWitt equation as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
(126 reference statements)
0
32
0
Order By: Relevance
“…For the three models at hand, we can solve (A5) analytically well inside the DE dominated regime, i.e., for t ≥ t * we have H 2 ≈ (κ 2 /3)ρ d , obtaining for each case the potential [40,41,[93][94][95] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the three models at hand, we can solve (A5) analytically well inside the DE dominated regime, i.e., for t ≥ t * we have H 2 ≈ (κ 2 /3)ρ d , obtaining for each case the potential [40,41,[93][94][95] …”
Section: Discussionmentioning
confidence: 99%
“…In these works, it was concluded that once the Universe enters in a genuinely quantum phase; i.e., where coherence and entanglement effects are important, the Universe would evade a doomsdayà la rip. This applies even to the smoother version of these singular behaviours corresponding to a LSBR [41] (see also [43][44][45][46][47]). …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as energy density diverges in all the cases presented, one might expect that quantum effects become important at some point in the future evolution. In fact, a quantum analysis shows that in all cases, the classical abrupt event can be avoided from a quantum point of view [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding potential has a quadratic dependence with the scalar field, as given in Equation (15). We notice that the obtained potential show a lower dependence with respect to the scalar field, φ, when comparing with the resulting potentials of other DE models like those that induce the BR and LR events [46,47]. We could affirm that the stronger is the dependence of the potential V(φ) with respect to φ, the more relevant are the divergences of the cosmological variables.…”
Section: Discussionmentioning
confidence: 96%